The Psychometric Properties of the Cone Evasion Walk Test in Patients With Knee Osteoarthritis. - Sevik Kacmaz, Kevser; Unver, Bayram; Karatosun, Vasfi; Hilton, Claudia (Occupational Therapy International, 2026)
Background: Knee osteoarthritis can impair mobility, gait, and balance and increase the risk of falls. The Cone Evasion Walk Test (CEW) is a comprehensive test that evaluates mobility, dynamic balance, and fall risk by assessing the ability to walk and turn in all directions while evading obstacles. It incorporates cognitive, sensory, visual, and various neuromusculoskeletal functions. This study was aimed at estimating the validity, reliability, and feasibility of the CEW in patients with knee osteoarthritis. Methods: Thirty‐six patients with knee osteoarthritis underwent two CEW trials on the same day. The Timed Up and Go Test and the Western Ontario and McMaster Universities Arthritis Index (WOMAC) were used. The intraclass correlation coefficient (ICC 2,1), standard error of measurement (SEM95), and smallest detectable change (SDC95) were calculated to assess reliability and measurement precision. Spearman′s correlations determined concurrent validity. The feasibility of the CEW was assessed based on completion rate, adherence, acceptability, practicality, and adverse effects. Results: The CEW demonstrated almost perfect within‐day (intrasession) reliability and moderate concurrent validity (r = 0.58 [95% CI: 0.317, 0.766], p < 0.001). The ICC (2,1), SEM95, and SDC95 for the CEW were 0.97 (0.87–0.99), 0.73 (0.59–0.95), and 2.02 (1.63–2.63), respectively, with 95% CI. The CEW was also found to be highly feasible. Conclusion and Implications of Key Findings: The findings support the use of the CEW to assess patients with knee OA. Our analysis revealed within‐day (intrasession) reliability, moderate concurrent validity, and high feasibility of the CEW. Given its convenience, short administration time, and minimal space and equipment requirements, the CEW may be used by occupational therapists as a complementary performance‐based measure within a broader occupation‐centered assessment to identify mobility‐related safety barriers and monitor interventions aimed at supporting participation in daily activities and community mobility.